2011
DOI: 10.1183/09031936.00184010
|View full text |Cite
|
Sign up to set email alerts
|

Association between domestic mould and mould components, and asthma and allergy in children: a systematic review

Abstract: Critical reviews over the past 10 yrs have found increased respiratory and allergic health outcomes for children living in damp and mouldy environments. However, recent studies have suggested that early childhood exposure to specific mould components may actually protect children from developing allergy.We conducted a systematic review of observational studies published in English from January 1980 to July 2010. This review was conducted according to systematic guidelines for Metaanalyses of Observational Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(124 citation statements)
references
References 94 publications
(172 reference statements)
7
108
3
3
Order By: Relevance
“…A recently published 10-year longitudinal study of adults in Uppsala, Sweden, found that signs of dampness in floor construction of any workplace building during follow up (cumulative exposure) were associated with incidence of mucosal symptoms (OR=2.43) including nasal catarrh, nasal obstruction, dryness in throat, sore throat or irritating cough [25]. Although the exact mechanism is unknown, it has been generally agreed that home mold or dampness is a risk factor for children's allergic diseases including asthma [26][27][28][29]. On the other hand, a recently published longitudinal study from Sweden found that self reported dampness or mold could be biased, since the baseline findings of a strong association between dampness and allergies disappeared in the follow-up study 5 years later [30].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published 10-year longitudinal study of adults in Uppsala, Sweden, found that signs of dampness in floor construction of any workplace building during follow up (cumulative exposure) were associated with incidence of mucosal symptoms (OR=2.43) including nasal catarrh, nasal obstruction, dryness in throat, sore throat or irritating cough [25]. Although the exact mechanism is unknown, it has been generally agreed that home mold or dampness is a risk factor for children's allergic diseases including asthma [26][27][28][29]. On the other hand, a recently published longitudinal study from Sweden found that self reported dampness or mold could be biased, since the baseline findings of a strong association between dampness and allergies disappeared in the follow-up study 5 years later [30].…”
Section: Discussionmentioning
confidence: 99%
“…Airborne microorganisms have a tendency to aggregate into particles of different sizes depending on source, species, relative humidity and the mechanism of aerosolization [26,36]. Several studies have indicated that the presence of fungi, bacteria and endotoxin in the indoor environment is associated with serious inflammation-related health risks such as asthma, allergies and respiratory discomfort [18,32,58]. Furthermore, several studies indicate that dose response relationship between exposure to microorganisms and the development of asthma exacerbate the symptoms [16,19,28,31,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these microbial agents were quantified in this study. Fungal genera typically found within the indoor environment are sources of potent allergens and inflammogens (22), and several epidemiological studies have coupled fungal exposure with asthma, allergy, and sick building syndrome (5,8,21,45,56). Exposure to bacteria has been associated with blocked nose and eye symptoms (14).…”
mentioning
confidence: 99%